TINJAUAN YURIDIS SISTEM PEMILIHAN UMUM ANGGOTA DEWAN PERWAKILAN RAKYAT PADA ERA ORDE BARU DENGAN ERA REFORMASI - Indra, Mexsasai; ', Ismail; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Electoral system adopted in the general election Members of Parliament in the New Order era to the era of the Reformation have differences in its implementation, the electoral system in the New Order is using a proportional system is closed lists of candidates and in the reform era that is proportional to the open list of candidates, which system that applied in that era have weaknesses and strengths in its implementation, thus need to review the electoral system the legislature in each era, whether it leads towards a democratic election. The purpose of this thesis, namely; First, to determine the electoral system Members of the House of Representatives in the New Order era to the era of reform. Second, to determine the strengths and weaknesses of the electoral system Members of the House of Representatives in the New Order era to the era of reform.This research is done by using an approach that is normative, because in this study the authors conducted research on the history of law and comparative law. While the source of the data used is using secondary data. Data collection techniques in this study the authors use the method of assessment literature or documentary studies and data analysis using deductive method is to analyze the problems of the general form into special shapes.Results of the study are: First, The electoral system used in the New Order Era is using stelsel proportional system with closed lists of candidates, voters vote for the party, and the party to vote for the candidate with the highest sequence number. While in the Reform Era, the electoral system used a proportional electoral system with open candidate list, voters may vote directly to the selected candidate. Second, the strengths and weaknesses of the electoral system in the New Order era and Reform, the advantages of the electoral system in the new order, namely, to produce security and order in the implementation and flexible, weakness namely electoral system is very close to the shadow of government intervention, not of transparency, this system affects the responsibility of legislators, while the excess electoral system reform era that is very democratic, open competition is positive for candidates, and weaknesses are, so complicated that people confused, complicated calculations voice, hamper the strengthening of democracy. First author's suggestion, it is recommended that every election changed the electoral system in use continues to meet the electoral system which is fitted applied in Indonesia Secondly, the elections that took place must be transfaransi and no intervention, the government must remain neutral in elections held in this country.Keywords: The electoral system-Members of Parliament-New Orde and Reform Era